120k views
4 votes
24. Simplify the expression: z2 – z(z + 3) + 3z a. 2z2 + 6z b. z + 3 c. 6z d. 0

2 Answers

1 vote
Simplifying the given equation ⤵


➡ z² - z( z + 3 ) + 3z


=> z² - z( z ) - z( 3 ) + 3z


=> z² - ( z × z ) - ( z × 3 ) + 3z


=> z² - z² - 3z + 3z



= > \cancel{ {z}^(2) } - \cancel{ {z}^(2) } + \cancel{3z} - \cancel{3z}


=> 0





Hence, option ( d ) is correct that is 0
User Brian Kiernan
by
4.8k points
2 votes

For this case we have the following expression:


z ^ 2 - z (z + 3) + 3z

By doing distributive property we have:


z ^ 2 - z ^ 2 - 3z + 3z

Then adding similar terms we have:


(z ^ 2 - z ^ 2) + (- 3z + 3z)

Rewriting:


(0) + (0)

Therefore, the simplified expression is:


0

Answer:

The simplified expression is:

d. 0

User Jmnwong
by
6.0k points